Impact of KLIBOR futures on the performance of banks in Malaysia - Ng, Joey Lan Hua (2025)
This study investigates the impact of Kuala Lumpur Interbank Offered Rate (KLIBOR) futures on the financial performance of banks in Malaysia, focusing specially on return on assets (ROA), return on equity (ROE), and net interest margin (NIM). Utilizing a panel data analysis with information of eight local conventional banks in Malaysia, covering a period of five years from 2019 to 2023, this research employs both fixed and random effects models to control for time invariant and time variant bank specific characteristics allowing a comprehensive assessment of the relationship between KLIBOR futures and bank profitability. The study reveals that while KLIBOR futures serve as a critical risk management tool to hedge against interest rate fluctuations, their influence on return on assets (ROA), return on equity (ROE), and net interest margin (NIM) is complex and differs among banks. Findings show a marginally negative correlation between the Q index - a pricing model for interest rates futures, and profitability measures (ROA and ROE), though non-performing loan (NPL) ratios, do not significantly impact these measures. The results suggest that KLIBOR futures may offer limited direct benefits to financial performance, highlighting the need for diversified risk management strategies. This study contributes to the empirical literature on interest rate derivatives in emerging markets, particularly in the context of Malaysian banking industry, providing understandings into the role of KLIBOR futures within the broader framework of the financial performance and risk mitigation.